Deleterious missense variants in the aflatoxin biosynthesis genes explain the low toxicity of Aspergillus flavus from infected rice. (March 2021) - Albakri, Ali H.; Al-Shuhaib, Mohammed Baqur S.; Alwan, Sabah L.; AbdulAzeez, Sayed; Borgio, J. Francis
Abstract: Aspergillus flavus is one of the most natural contaminants of the improperly stored rice grains. It produces several secondary metabolites, like aflatoxins, which are well known hepatotoxic, hepatocarcinogenic and mutagenic agents. This study describes the in silico consequences of the missense mutations identified in several genes of aflatoxins biosynthesis in rice-contaminating A. flavus isolates. In the in vitro portion of the study, aflatoxins production profile was measured, and PCR-single strand-conformation polymorphism (SSCP)-sequencing method was used to genotype the studied genetic loci: afl P, afl M, afl R, PEP, and cob . Results showed aflatoxigenic potential in 79 out of 109 A. flavus isolates. Twenty-two missense and fifty-five synonymous mutations were found to be distributed variably on the studied loci. In the in silico portion of this study, several computations were utilized to predict the effect of each observed missense mutation on proteins structure, function, and stability. Seven mutations (O-methyl transferase: p.G256C; ver-1 dehydrogenase: p.K179 N and p.V183L; aspergillopepsin-1: p.P137L, p.S138F, p.G154C, and p.S158C) were found to be highly deleterious among the missense variants with damaging effects on their proteins' structure and function. In contrast to these detected variations in the aflatoxigenic loci, all missense mutations in the control non-aflatoxigenic cob gene were found to be neutral. These findings indicated that the observed mutations may reduce the concomitant biohazard of their biosynthesized aflatoxins. The current findings suggest that the naturally available variants may reduce or eliminates the dangerous consequences of aflatoxins upon ingesting the rice infected with A. flavus . To the best of our knowledge, this study is the first comprehensive report to analyze the missense mutations on the aflatoxin biosynthesis genes using in vitro and the state-of-art bio-computational tools. Highlights: In contrast to variations in aflatoxigenic loci of  Aspergillus flavus, missense mutations in the control  cob  gene were found to be neutral. The observed mutations in rice-infecting  Aspergillus flavus  may reduce the biohazard of biosynthesized aflatoxins of these isolates. The natural variants may reduce or eliminates the dangerous consequences of aflatoxins upon ingesting the rice infected with  A. flavus .